Caregiving, carebots, and contagion - Brannigan, Michael C., 1948- (Revolutionary Bioethics., 2022)
"Would you want to be cared for by a robot? Michael C. Brannigan's Caregiving, Carebots, and Contagion explores caring robots' lifesaving benefits, particularly during contagion, while probing the threat they pose to interpersonal engagement and genuine human caregiving. As our COVID-19 purgatory lingers on, caring robots will join our nursing and healthcare frontlines. Carebots can perform lifesaving tasks to minimize infection, safeguard vulnerable persons, and relieve caregivers of certain burdens. They also spark profound moral and existential questions: What is caring? How will we relate with each other? What does it mean to be human? Underscoring carebots' hands-on benefits, Brannigan also warns us of perils. They can be a dangerous lure in a culture that settles for substitutes and venerates the screen. Alerting us to the threatening prospect of carebots becoming our surrogate for interpersonal connection, he maintains they are not the culprits. The challenge lies in how we relate to them. While they beneficially complement our caregiving, carebots cannot replace human caring. Caring is a fundamentally human act and lies at the heart of ethics. As humans, we have a binding moral responsibility to care for the Other, and genuine caring demands our embodied, human-to-human presence"--